Tanggung Jawab Notaris terhadap Keabsahan Akta Otentik dalam Perspektif Hukum Perdata - Az Zahra Eka Putri; Dewi Ulfa Uluwiyah; ⁠Misnadah; Shelomita Retno Wulandari; Tomi Henrayana (Jurnal Hukum Lex Generalis, 2026)
Notarial deeds as authentic instruments possess perfect evidentiary value in civil law. The validity of an authentic deed depends on the fulfillment of formal and material requirements in accordance with applicable laws and regulations. Issues arise when errors or negligence occur in the drafting process, resulting in the deed failing to meet validity requirements. This study aims to analyze the responsibility of notaries for the validity of authentic deeds and the legal consequences arising when such deeds fail to meet validity requirements from a civil law perspective. This research employs a normative legal method using statutory and conceptual approaches. The results indicate that notaries bear significant responsibility in ensuring the validity of deeds through the application of the prudential principle. Deeds that fail to meet validity requirements may lose their authenticity, thereby affecting their evidentiary value and resulting in legal consequences such as nullity, voidability, or degradation into private deeds. Therefore, professionalism and diligence of notaries are essential to ensure legal certainty.